Some environmental and social aspects of water resources development - Hargreaves, George H., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1996)
Carbon emissions from the use of fossil fuels are increasing. Global warming continues resulting in more violent and destructive storms. The world population is increasing by nearly 90 million annually. Forests are rapidly being destroyed in the developing countries. Irrigated area per capita and food grain production are declining. The competition from the cities for water is increasing. Many aquifers are being polluted and/or over pumped. However, deforestation, soil erosion, population growth, and flooding decrease with water resources and other economic developments. Large new areas can be brought into agricultural production through the construction of irrigation and drainage facilities. There are many good sites for large dams in the developing countries. These dams can be used for hydropower, flood storage, irrigation supplies, and domestic water. Hydropower is clean energy and should be substituted for a large portion of the present use of fossil fuels. Benefits from fertilizers increase with increasing availability of water. Governments and politicians are poor managers of water resources. Many large development possibilities are international in scope. Electrical grids should be more interconnected and possibly continental in scope. Few if any developing countries have an institutional capacity for coordinated water resources developments. The international lending agencies should give priority to the financing of national and international water resources development authorities that at least partially privatize water resource management. Also priority should be given to those projects and activities that improve the environment.
1996 USCID water management conference
Environmental and social aspects
Not digitized by CSUL Digital Services.
Presented at Competing interests in water resources - searching for consensus: proceedings from the USCID water management conference held on December 5-7, 1996 in Las Vegas, Nevada.